Muscle soreness and fatigue and their associations with internal and external load measures in professional soccer players - Clemente, F. M. (Journal of Human Sport & Exercise, 2019)
The purpose of this study was to examine the correlations between perceived fatigue and muscle soreness (DOMS) and training load measures collected on the same day (0d), as well as one day (+1d), two days (+2d) and three days (+3d) before a well-being report. Twenty-three professional soccer players (24.9±3.5 years old; height: 168.8±41.4 cm) from a team competing in the Portuguese first league were daily monitored for one month. Hooper questionnaire, CR10 Borg`s scale, and 10-Hz GPS units were daily applied to track the perceived well-being of players and the load impact of the sessions. The correlations between fatigue and DOMS on the same day with the load measures revealed large inverse correlations between fatigue and total distance (r=-0.53), running distance (r=-0.56), and player load (r=-0.66); a moderate inverse correlation between DOMS and player load (r=-0.44). Interestingly, correlations between fatigue and DOMS and the training load measures of the training session two days before the well-being report revealed large positive correlations between fatigue and total distance (r=0.52), as well as large and positive correlations between DOMS and total distance (r=0.58) and DOMS player load (r=0.60). The results suggest that smaller levels of fatigue and DOMS may potentiate a greater availability to support greater loads during training sessions and that the effect of load on fatigue and DOMS is delayed rather than immediate.